2020
DOI: 10.1257/aer.20190460
|View full text |Cite
|
Sign up to set email alerts
|

Discounts and Deadlines in Consumer Search

Abstract: We present a new equilibrium search model where consumers initially search among discount opportunities, but are willing to pay more as a deadline approaches, eventually turning to full-price sellers. The model predicts equilibrium price dispersion and rationalizes discount and full-price sellers coexisting without relying on ex ante heterogeneity. We apply the model to online retail sales via auctions and posted prices, where failed attempts to purchase reveal consumers' reservation prices. We find robust evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…This assumption is motivated in our environment by idiosyncratic differences in willingness to pay across bidders that can arise due to differences in ability to pay, outside option opportunities, or urgency with which the phone is needed. For example, Coey, Larsen, and Platt (2020) demonstrated that eBay auction bidding behavior is consistent with bidders having idiosyncratic, independent deadlines by which they need a particular item.…”
Section: Application To Used Smartphone Auctionsmentioning
confidence: 99%
“…This assumption is motivated in our environment by idiosyncratic differences in willingness to pay across bidders that can arise due to differences in ability to pay, outside option opportunities, or urgency with which the phone is needed. For example, Coey, Larsen, and Platt (2020) demonstrated that eBay auction bidding behavior is consistent with bidders having idiosyncratic, independent deadlines by which they need a particular item.…”
Section: Application To Used Smartphone Auctionsmentioning
confidence: 99%
“…Consider one of the CCN managers with r units of residual participation time. Similar to [30], aggressive bidding strategy is considered, where the CCN managers bid more values as they approach the deadline. In this case, the instantaneous bid of a CCN manager can be modeled as follows:…”
Section: Interactions Between Ccn Managers and Cpsmentioning
confidence: 99%
“…The expected utility of a CCN 13. A simplified version of our analysis is presented in [30] for a retail market, where the focus is on the second-price payment mechanism. In their model, the offered prices of the sellers are not incorporated into the analysis which simplifies their model and derivations.…”
Section: First-price Analysismentioning
confidence: 99%
“…To the best of our knowledge only Moraga-González and Watanabe (2016) and Garcia et al (2015) introduce capacity constraints in markets in which consumers search sequentially over different producers offering heterogeneous products but they abstract from dynamic considerations. Similarly, Coey et al (2016) study a random search model in which buyers search over time for better prices and sellers sort themselves into a faster auction market and a slower posted-price market, but do not face capacity constraints. 5…”
Section: Related Literaturementioning
confidence: 99%